Scropolioside B Inhibits IL-1β and Cytokines Expression through NF-κB and Inflammasome NLRP3 Pathways - Zhu, Tiantian; Zhang, Liuqiang; Ling, Shuang; Duan, Ju; Qian, Fei; Li, Yiming; Xu, Jin-Wen (Mediators of Inflammation, 2014)
Chronic inflammation is associated with various chronic illnesses including immunity disorders, cancer, neurodegeneration, and vascular diseases. Iridoids are compounds with anti-inflammatory properties. However their anti-inflammatory mechanism remains unclear. Here, we report that scropolioside B, isolated from a Tibetan medicine (Scrophularia dentata Royle ex Benth.), blocked expressions of TNF, IL-1, and IL-32 through NF-κB pathway. Scropolioside B inhibited NF-κB activity in a dose-dependent manner with IC50 values of 1.02 μmol/L. However, catalpol, similar to scropolioside B, was not effective in inhibiting NF-κB activity. Interestingly, scropolioside B and catalpol decreased the expression of NLRP3 and cardiolipin synthetase at both the mRNA and protein level. Our results showed that scropolioside B is superior in inhibiting the expression, maturation, and secretion of IL-1β compared to catalpol. These observations provide further understanding of the anti-inflammatory effects of iridoids and highlight scropolioside B as a potential drug for the treatment of rheumatoid arthritis and atherosclerosis.